A realização variável da lateral pós-vocálica /l/ em comunidades baianas do projeto atlas linguístico do Brasil (alib) - Dos Santos, Robevaldo Correia (2017)
Based on the theoretical and methodological assumptions of labovian sociolinguistics and the multidimensional geolinguistics, this research aims to investigate the variable realization of the post-vocalic lateral / l / in the position of syllabic coda in Bahia communities of the Linguistic Atlas of Brazil Project (ALiB Project). For this purpose, we analyze a corpus with 24 interviews with natural informants from the following locations, members of the ALiB Project network: Euclides da Cunha, Barra, Jacobina, Seabra, Santo Amaro and Santa Cruz Cabrália. According to the methodology of the ALiB Project, the informants are stratified by both sexes, with four informants in each city, divided into two age groups (range 1 – 18 to 30 years old and range 2 – 50 to 65 years old), graduated, at most, until High School. To carry out the research, the following hypotheses were raised: the / l / in the final position of the syllable is variable in the speech of the investigated communities, with the vocalized variant [w] already widely disseminated in the speech from Bahia cities, but not in a categorical way; the interaction between linguistic and social factors in the variation of / l / is the vector of this phenomenon; the variation of / l / points to a change in progress. The results point to a tendency to change, in which the erasing of the dependent variable has been abandoned by the younger informants in favor of the vocalized variant, so that the implementation of the vocalization presents different stages in each of the selected localities